A field guide to lies : critical thinking with statistics and the scientific method - Levitin, Daniel J., 1957- ([New York] : Dutton, 2016)
We are bombarded with more information each day than our brains can process—especially in election season. It’s raining bad data, half-truths, and even outright lies. Daniel J. Levitin shows how to recognize misleading announcements, statistics, graphs, and written reports, revealing the ways lying weasels can use them. Levitin groups his field guide into two categories—statistical information and faulty arguments—ultimately showing how science is the bedrock of critical thinking. Readers learn to avoid the extremes of passive gullibility and cynical rejection. His accessible guide helps anyone wake up to a whole lot of things that aren’t so—and catch some weasels in their tracks!
Kniha nabízí praktický návod, jak se orientovat v záplavě informací a rozpoznávat zavádějící tvrzení, statistické manipulace a logické klamy. Autor, srozumitelně vysvětluje principy vědecké metody a kritického myšlení, které pomáhají čtenáři činit informovaná rozhodnutí a vyhnout se pasivní důvěřivosti i cynickému odmítání faktů.
Terminologický slovník
"Previously published as a Dutton hardcover in September 2016 as A field guide to lies and as a trade paperback in 2017 as Weaponized lies"—Rub titulní stránky
První brožované vydání: 2019
Obsahuje bibliografické odkazy a rejstřík
Keywords: kritické myšlení; usuzování; manipulace (psychologie); dezinformace; příručky; critical thinking; reasoning; manipulation (psychology); disinformation; handbooks and manuals